Enhancing surgical safety through surgical instruments repair technicians’ training: recent experience from Nigeria - Udeigwe-Okeke, Chisom R.; Seyi-Olajide, Justina O.; Obisesan, Aderonke O.; Miles, Keith; Obi, Nkeiruka; Ameh, Emmanuel A. (Frontiers in Public Health, 2025)
BackgroundFaulty or poorly maintained surgical instruments increase risks of complications, prolong operating times, and reduce efficiency, especially in low- and middle-income countries (LMICs). To address this, Nigeria introduced the Surgical Instruments Repair Technicians (SIRT) program, to improve instrument safety.ObjectiveThis study evaluated the SIRT program’s initial impact, sustainability, and scalability for improved surgical instrument maintenance in LMICs.MethodsThe program was deployed in two phases. Phase one involved online theoretical and hands-on training for biomedical technicians and operating room/central sterile supply department nurses from Smile Train partner and public hospitals across Nigeria’s six geopolitical zones. Participants were provided repair kits to establish institutional workbenches. Phase two focused on expanding training with a one-week hands-on program. Data on demographics, training feedback, and repair outcomes were collected.ResultsA total of 36 participants completed training (24 in phase one, 12 in phase two), evaluating 1,623 instruments with a 99.6% successful repair rate. Post-training surveys showed that 83.3% of participants felt more confident identifying faulty instruments, and 95.8% reported adequate repair skills. Institutional workbenches were established in 50% of hospitals, and repair drives were conducted within institutions and neighboring hospitals.ConclusionThe program demonstrated significant potential for improving surgical instrument maintenance and enhancing safety in LMICs. Integrating the program into hospital budgets could support sustainable expansion.